A genome-wide screen for susceptibility loci in ankylosing spondylitis. - Brown, M; Pile, K; Kennedy, L; Campbell, D; Andrew, L; March, R; Shatford, J; Weeks, D; Calin, A; Wordsworth, B (1998)
OBJECTIVE: To localize the regions containing genes that determine susceptibility to ankylosing spondylitis (AS). METHODS: One hundred five white British families with 121 affected sibling pairs with AS were recruited, largely from the Royal National Hospital for Rheumatic Diseases AS database. A genome-wide linkage screen was undertaken using 254 highly polymorphic microsatellite markers from the Medical Research Council (UK) (MRC) set. The major histocompatibility complex (MHC) region was studied more intensively using 5 microsatellites lying within the HLA class III region and HLA-DRB1 typing. The Analyze package was used for 2-point analysis, and GeneHunter for multipoint analysis. RESULTS: When only the MRC set was considered, 11 markers in 7 regions achieved a P value of < or =0.01. The maximum logarithm of odds score obtained was 3.8 (P = 1.4 x 10(-5)) using marker D6S273, which lies in the HLA class III region. A further marker used in mapping of the MHC class III region achieved a LOD score of 8.1 (P = 1 x 10(-9)). Nine of 118 affected sibling pairs (7.6%) did not share parental haplotypes identical by descent across the MHC, suggesting that only 31% of the susceptibility to AS is coded by genes linked to the MHC. The maximum non-MHC LOD score obtained was 2.6 (P = 0.0003) for marker D16S422. CONCLUSION: The results of this study confirm the strong linkage of the MHC with AS, and provide suggestive evidence regarding the presence and location of non-MHC genes influencing susceptibility to the disease.